Position and shape estimation using double integration of acceleration - Yong, Ching Yee; Rubita Sudirman,; Chew, Kim Mey (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study investigates and acts as a trial clinical outcome for human motion and hand behaviour analysis in consensus of subject’s habit related quality of life. It was developed to analyse and access the quality of human hands motion that can be used in hospitals, clinics and human motion researches. It aims to establish how widespread the quality of life effects of human motion. An experiment was set up in a laboratory environment with conjunction of analysing human hand motion and its habit. Sensors are attached on both wrists. The instruments demonstrate adequate internal consistency of findings: 1. it is hard for subject to draw a perfect circle whether using left or right hand and this is supported by descriptive statistical data and simulation of drawings. 2. Subject’s left hand (right handed) unable to draw a perfect circle or square. These two drawings are looks alike and it is supported by double integration technique. A simple and informative representation for statistical data, simulation of drawings were developed to demonstrate the results.